The strategic choice of payment method in corporate acquisitions: The role of collective bargaining against unionized workers - Chen, I-Ju; Chen, Yan-Shing; Chen, Sheng-Syan (Journal of Banking & Finance, 2018)
Acquirers facing strong union power tend to acquire target firms with cash rather than equity or a mix of cash and equity. A one standard deviation increase in the union power faced by the acquirer increases the odds of choosing cash payment by a factor ranging from 1.26 to 1.57. The effect is stronger when: the acquiring firm is located in states without the right-to-work laws; the interests of managers are more aligned with shareholders in acquiring firms; and acquiring firms’ asset specificity is high. When union power is strong, acquirers making cash payment are associated with a significantly positive announcement return. In addition, they are less likely to experience labor strikes or declines in operating performance, and more likely to obtain wage concessions in collective bargaining in the post-acquisition period than acquirers using other methods of payment. These findings suggest that cash payment allows acquirers to reduce excess liquidity and strengthen their bargaining power with unions.